Multiplexing High‐Content Flow (HCF) and Quantitative High‐Throughput Screening (qHTS) to Identify Compounds Capable of Decreasing Cell Viability, Activating Caspase 3/7, Expressing Annexin V, and Changing Mitochondrial Membrane Integrity. Issue 3 (1st October 2013) - Mathews, Lesley A.; Keller, Jonathan M.; McKnight, Crystal; Michael, Sam; Shinn, Paul; Liu, Dongbo; Staudt, Louis M.; Thomas, Craig J.; Ferrer, Marc
Abstract: High‐content flow (HCF) screening systems, such as the iQue Screener and HTFC Screening System from IntelliCyt, have facilitated the implementation of flow cytometry assays for high‐throughput screening. HCF screening systems enable the use of smaller sample volumes and multiplexed assays to simultaneously assess different cellular parameters from a single well. This becomes invaluable when working with cells or compounds that are available in limited quantities or when conducting large‐scale screens. When assays can be miniaturized to a 384‐ or 1536‐well microplate format, it is possible to implement dose‐response‐based high‐throughput screens, also known as quantitative HTS or qHTS. This article describes how qHTS at the new National Center for Advancing Translational Science (NCATS) has been systematically coupled with the HTFC Screening System and Multimetric Apoptosis Screening Kit from IntelliCyt to biologically validate active compounds from primary cell proliferation screens using a model of diffuse large B cell lymphoma (DLBCL). Curr. Protoc. Chem. Biol . 5:195‐212 © 2013 by John Wiley & Sons, Inc.